2019
DOI: 10.1055/a-1010-5581
|View full text |Cite
|
Sign up to set email alerts
|

A long (7 cm) prophylactic pancreatic stent decreases incidence of post-endoscopic papillectomy pancreatitis: a retrospective study

Abstract: Background and study aims  Endoscopic papillectomy (EP) is a minimally invasive treatment for ampullary neoplasms and is recognized as an alternative treatment to surgical resection; however, there are few reports on a suitable pancreatic stent (PS) after EP for preventing pancreatitis. The aim of this study was to evaluate the efficacy of a long PS after EP. Patients and methods  In this retrospective single-center study, 39 patients with pathologically proven ampullary neoplasms who underwent EP between Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…7,8,[49][50][51]56,59,60,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] In addition, the cumulative incidence rates of severe cases from the reports with severity grades were 10.2% for pancreatitis, 7.3% for bleeding, 12.5% for perforation, and 0% for cholangitis. 8,[49][50][51]56,59,60,[67][68][69][70][71][72][73][74][75][76][78][79][80][81] Moreover, four cases of death were reportedly attributed to early AEs, comprising two cases of pancreatitis and two cases of perforation. 67,75,81 The differences in the incidence rates may be attributed to differences in AE definitions and investigative methods and modalitie...…”
Section: Commentarymentioning
confidence: 99%
“…7,8,[49][50][51]56,59,60,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] In addition, the cumulative incidence rates of severe cases from the reports with severity grades were 10.2% for pancreatitis, 7.3% for bleeding, 12.5% for perforation, and 0% for cholangitis. 8,[49][50][51]56,59,60,[67][68][69][70][71][72][73][74][75][76][78][79][80][81] Moreover, four cases of death were reportedly attributed to early AEs, comprising two cases of pancreatitis and two cases of perforation. 67,75,81 The differences in the incidence rates may be attributed to differences in AE definitions and investigative methods and modalitie...…”
Section: Commentarymentioning
confidence: 99%
“…However, early stent dislodgment may result in delayed-onset pancreatitis 14 . Delayed-onset pancreatitis because of the secondary obstruction of flow after resection or a direct burn effect in the pancreatic parenchyma is a serious complication, particularly in cases of EP 28 , 29 . Therefore, the inner flange is important for preventing early dislodgment, though the optimal stenting time is still uncertain 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The study population included more patients who underwent EP than in previous studies. However, the risk of pancreatitis is high after EP 28 , 29 , 31 . The rates of PEP in our heterogeneous study population were comparable to that reported in high-risk patients with pancreatic duct stents 11 , 13 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…De acuerdo con un estudio previo, si el extremo intraductal está a nivel de la cabeza se incrementa el riesgo de pancreatitis (OR: 3.8; IC 95%: 1.1-12.9; p = 0.03) 66 . Un escenario especial es el grupo de pacientes en quienes se realiza ampulectomía endoscópica, donde las de 7 cm parecen tener una mayor eficacia comparadas con las de 5 cm (OR: 0.16; IC 95%: 0.27-0.94; p = 0.042) 67 .…”
Section: Prótesis Plásticas Pancreáticasunclassified